Environmental and Calcification Impacts on the δ18O and δ2H Values of Cold‐Water Coral Skeleton Fluid Inclusions - Yao Wu; Dana Hölkermann; Amrei Grund; Sophie Warken; Norbert Frank (Geochemistry, Geophysics, Geosystems)
Abstract Coral skeletons exhibit a complex composition of mineral and organic components, with the water content playing a significant role in their structure. Water associated with organic matrices constitutes the major share, whereas nonstructural water (skeleton inclusion water) is present in much smaller amounts, typically less than 0.5 wt% of the coral skeleton. The isotopic composition of this water may reflect biomineralization processes or environmental conditions during skeleton formation. Here, we present fluid inclusion hydrogen and oxygen isotopic compositions of cold‐water coral skeletons from Angola and Iceland. We confirmed the kinetic isotope fractionation when coral skeletons were crushed at a temperature of 120°C using a cavity ring‐down spectroscopy analyzer. δ18O and δ2H values are not reproducible across analytical setups with varying temperature parameters. When coral fragments are encapsulated in a glass tube, the amount of released water and its isotopic signature are far more reproducible. δ18O and δ2H values of coral skeleton inclusion water from Angola show no significant differences between the Holocene and the last glacial period. The δ2H values are characterized by strong isotopic fractionation compared to seawater. Our study highlights that current methods do not adequately capture the variability in the initial δ18O and δ2H of the “quasi‐free” skeleton inclusion water in coral aragonite. It is also possible that there are varying degrees of exchange of skeleton inclusion water with seawater. A better understanding of the coral calcification process is still necessary to establish a clearer link between the isotopic compositions of seawater and skeleton inclusion water.